The power of social networking sites: Student involvement toward education - M. Norhailawati; Lina Handayani; HU Kalsum; Zainuri Saringat; A. Aidahani; SH Bakri; Rully Charitas Indra Prahmana (International Journal of Evaluation and Research in Education (IJERE), 2019)
Social networking web sites is not a new medium for users. The growth of this media helps students communicate and socialize with their friends or followers and used for education. The retention number of students is an issue or real problem in higher educational institutions since it is related to institution overall performance. This research focused on how students’ involvement in social network web site for educational purposes can have a positive effect to their studies and can help institution to retain number of students in the institution. During the research study, students did give full cooperation and involvement in the group that created and dedicated to their collaborative learning. Facebook is the social networking website that used to support learning. The research method applied was survey and the questionnaires distributed to 40 students who got probations result (the Cumulative Grade Point Average (CGPA) was below 2.00) from various academic programs. The result showed that social network website plays an important role in education. The finding also showed that the probation students improve their CGPA and status, while the institution able to maintain their student retention number.